2019
DOI: 10.3389/fpls.2019.00438
|View full text |Cite
|
Sign up to set email alerts
|

NEP-TC a rRNA Methyltransferase Involved on Somatic Embryogenesis of Tamarillo (Solanum betaceum Cav.)

Abstract: Somatic embryogenesis (SE) is an important biotechnological tool for large-scale clonal propagation and for embryogenesis research. Moreover, genetic transformation and cryopreservation procedures in many species rely on efficient SE protocols. We have been studying different aspects related to SE induction and somatic embryo development in tamarillo ( Solanum betaceum Cav.), a small tree from the Solanaceae family. Previous proteomic analyses identified a protein (NEP-TC, 26.5 kDa) cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…The NEC calli show a greater similarity in the mass ratios but a higher disparity in total protein content. These observations are in accordance with previous studies of these types of calli that have shown EC and NEC callus to be morphologically distinct [31] and present the NEC calli as a highly hydrated tissue. Furthermore, previous studies have shown some differences at the proteomic level on similar callus lines [26] and quantitative and qualitative differences in EC-and NEC-callus-secreted proteins [32].…”
Section: Somatic Embryogenesis and Metabolite Profilesupporting
confidence: 93%
“…The NEC calli show a greater similarity in the mass ratios but a higher disparity in total protein content. These observations are in accordance with previous studies of these types of calli that have shown EC and NEC callus to be morphologically distinct [31] and present the NEC calli as a highly hydrated tissue. Furthermore, previous studies have shown some differences at the proteomic level on similar callus lines [26] and quantitative and qualitative differences in EC-and NEC-callus-secreted proteins [32].…”
Section: Somatic Embryogenesis and Metabolite Profilesupporting
confidence: 93%
“…Analysis of ICL cellular protein profiles revealed high expression levels of stress-related proteins [ 11 , 12 ], confirming the role of tissue culture systems in inducing molecular reprogramming. During recent experiments, S. betaceum ICL was grown efficiently as PCSs [ 13 ].…”
Section: Introductionmentioning
confidence: 92%
“…Sandra Correia investigated the role of the rRNA methyltransferase NEP-TC on somatic embryogenesis in Solanum betaceum Cav. and found that when NEP-TC was down-regulated, the induction level of somatic embryos was slightly increased [ 14 ]. In addition, recent advancements in transgenic technology are providing new insights on the regulation of callus formation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%